Effectiveness of Land Restoration in African’s Great Green Wall (GGW): Insight from Nigeria’s Frontline State - Idowu Oyemomi, Paul; Chado Salihu, Abdullahi; Musa Mshelia, Ayuba; Goma, Danbaba (Journal of Sustainable Natural Resources, 2025)
The Sahel region of Africa faces severe land degradation, compromising crucial ecosystem services vital for human well-being. In response, 11 African countries initiated the Great Green Wall (GGW) project to combat land degradation, with Nigeria, including Borno state, actively participating. This study focuses on evaluating GGW’s effectiveness in Borno state using Landsat imagery from 1993 to 2022. Data from Landsat satellites, specifically Landsat 4, 5, 7, and 8, were utilized alongside GIS tools like ArcGIS 10.8 for image classification and analysis. Microsoft Office aided in data visualization and report generation, while Google Earth Pro facilitated area calculation and feature confirmation. The analysis, employing NDVI trends and a two-way repeated measures ANOVA, revealed a non-significant impact of GGW on greening in the region (F-value: 0.665, p>0.05). Despite the implementation of GGW in Borno state, findings suggest limited effectiveness in mitigating land degradation. This underscores the need for reassessment and potential recalibration of GGW strategies to achieve desired ecological restoration outcomes in the Sahel region.